Modelling of water-to-gas hollow fiber membrane humidifier - Pandey, R.; Lele, A. (Chemical Engineering Science, 2018)
A microscopic mathematical model is developed for membrane based water-to-gas humidification by rigorously accounting for phase equilibrium between the membrane and water phases as well as membrane and gas phases in addition to the coupled heat and mass transfer occurring across the membrane. The model is then integrated along the length of a hollow fiber membrane humidifier in order to predict humidifier performance as a function of design variables, operating variables and operational strategies. For realistic values of membrane thickness and flow parameters, the model suggests that while membrane-gas interfacial resistance alone is crucial for heat transfer, the vapor transfer is governed by the combined resistances of diffusion within the membrane and membrane-gas interface. The model is validated against experimental data obtained using a commercial hollow fiber
Keywords: Coupled Heat and Mass; Fuel Cell Applications; Humidification; Phase equilibrium; Proton exchange membrane; Water-to-gas